Beyond comparison: sex and discrimination - Macklem, Timothy (Cambridge University, 2013)
In Beyond Comparison: Sex and Discrimination Timothy Macklem addresses foundational issues in the long-running debate in legal, political, and social theory about the nature of gender discrimination. He takes the highly original and controversial view that the heart of discrimination lies not in the unfavourable comparisons with the treatment and opportunities that men enjoy but rather in a denial of resources and opportunities that women need to lead successful and meaningful lives as women. Therefore, to understand what women need we must first understand what it is to be a woman." "By displaying an impressive command of the feminist literature as well as intellectual rigour, this work promises to be a milestone in the debate about gender equality and will interest students and professionals in the areas of legal theory and gender studies.